Implementation of Tunneled Peripherally Inserted Central Catheters Placement in Cancer Patients: A Randomized Multicenter Study - Sheng, Yuan; Yang, Li-Hong; Wu, Yan; Gao, Wei; Dongye, Sheng-Yi (Clinical nursing research, 2024)
This study sought to evaluate the impact of the subcutaneous tunneling technique on peripherally inserted central catheter (PICC) placement. We randomized 694 patients who needed PICC placement to either the tunneled PICCs (experimental group) or the non-tunneled PICCs (control group) from August to December 2021. The cumulative frequency of complications was assessed as the primary outcome. Secondary outcomes comprised of the amount of bleeding, catheter insertion time, self-reported pain score, and one-puncture success rate. After 6 months of follow-up, the tunneled PICCs group showed a significant decrease in the frequency of total complications, especially in infection (3.0% vs. 7.1%, = .021) and catheter-related thrombosis (3.3% vs. 8.3%, = .008), although approximately 0.5 ml bleeding and 3.5 min time were increased. This randomized multicenter study supports the efficacy of subcutaneous tunneling technology in reducing PICC-related complications, enhancing patient comfort, and encouraging using subcutaneous tunneling technology for PICC placement.